Neutron scattering in the biological sciences: progress and prospects. Issue 12 (3rd January 2019) - Ashkar, Rana; Bilheux, Hassina Z.; Bordallo, Heliosa; Briber, Robert; Callaway, David J. E.; Cheng, Xiaolin; Chu, Xiang-Qiang; Curtis, Joseph E.; Dadmun, Mark; Fenimore, Paul; Fushman, David; Gabel, Frank; et al.
Abstract : A wide variety of neutron scattering techniques can be applied to obtain information on the structure and dynamics of biological systems on multiple scales. Recent progress is summarized, as are hoped‐for future developments in the context of the advent of next‐generation neutron sources on various continents. Abstract : The scattering of neutrons can be used to provide information on the structure and dynamics of biological systems on multiple length and time scales. Pursuant to a National Science Foundation‐funded workshop in February 2018, recent developments in this field are reviewed here, as well as future prospects that can be expected given recent advances in sources, instrumentation and computational power and methods. Crystallography, solution scattering, dynamics, membranes, labeling and imaging are examined. For the extraction of maximum information, the incorporation of judicious specific deuterium labeling, the integration of several types of experiment, and interpretation using high‐performance computer simulation models are often found to be particularly powerful.